2010
DOI: 10.1053/j.gastro.2009.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Promotes Gastric Atrophy Through Suppression of Sonic Hedgehog

Abstract: Background & Aims-In both human subjects and rodent models, Helicobacter infection leads to a decrease in Shh expression in the stomach. Sonic Hedgehog (Shh) is highly expressed in the gastric corpus and its loss correlates with gastric atrophy. Therefore, we tested the hypothesis that proinflammatory cytokines induce gastric atrophy by inhibiting Shh expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 33 publications
2
93
0
5
Order By: Relevance
“…67 Gastric acid induces Shh gene expression. 56, , 68 69 Aberrant expression of Shh is involved in the pathogenesis of gastric diseases such as gastric atrophy, 70,71 hypergastrinemia and hyperproliferation of surface mucous cells. 72 All these studies will help us to better understand the molecular mechanism of gastric diseases and optimize the strategy of treatment.…”
Section: Activation Of the Hh Pathway In Gastric Cancermentioning
confidence: 99%
“…67 Gastric acid induces Shh gene expression. 56, , 68 69 Aberrant expression of Shh is involved in the pathogenesis of gastric diseases such as gastric atrophy, 70,71 hypergastrinemia and hyperproliferation of surface mucous cells. 72 All these studies will help us to better understand the molecular mechanism of gastric diseases and optimize the strategy of treatment.…”
Section: Activation Of the Hh Pathway In Gastric Cancermentioning
confidence: 99%
“…Progressive fundic hyperplasia was also observed in other mouse models of inflammation, such as the stomach‐specific IL‐1 β ‐overexpressing mouse,27 after chronic IL‐11 exposure,25 in Helicobacter felis ‐infected mice,44 and in gastrin‐KO and omeprazole‐treated mice that develop gastric bacterial overgrowth 45. In these models, the inflammatory cytokines are believed to downregulate sonic hedgehog expression,45 an important parietal cell morphogen, leading to parietal cell demise and loss of gastric acidity 19, 43.…”
Section: Discussionmentioning
confidence: 77%
“…It is reported that individuals carrying the IL-1β and TNFα risk genotype are likely to suffer GC (27). IL-1β promotes gastric atrophy through suppression of Sonic Hedgehog (28). The upregulation of IL-1β, IL-8 and COX-2 in patients with chronic gastritis has a significant clinical implication in gastric carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%